Supervisi Akademik Memoderasi Pengaruh Leadership Principal dan Motivasi Kerja terhadap Kinerja guru pada Guru SD Negeri di Kabupaten Batang - Junaedi; Robertus Basiya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of leadership principal, work motivation and academic supervision on teacher performance and the role of academic supervision as a moderator between leadership principal and work motivation on teacher performance in elementary school teachers in Batang Regency. The population in this study were 120 elementary school teachers in Batang Regency. The results showed that leadership principal had a positive and significant effect on teacher performance, work motivation had a positive and significant effect on teacher performance, academic supervision had a positive and significant effect on teacher performance, academic supervision did not moderate the influence of leadership principal on teacher performance, and academic supervision moderated the influence of work motivation on teacher performance.